The new army in training - Kipling, Rudyard 1865-1936 (Uniform Press Ltd., 2015)
On August 4th 1914, following the German invasion of Belgium, Britain declared war on Germany. During the autumn, Kipling wrote six articles about the training of the new British troops who had volunteered to fight. These were published in the Daily Telegraph in December 1914. Early in 1915 they were collected into a small booklet, published in the United Kingdom as The New Army in Training (price sixpence), and in the United States as The New Army. The articles include: The Men at Work; Iron into Steel; Guns and Supply; Canadians in Camp; Indian Troops; Territorial Battalions